Survey educational needs of 11-14 years old Girls about Sexual health - Poorandokht Afshary; Seyedeh Zahra Pazhohideh; Hamideh Yazdi Zadeh; Solmaz Mohammadi; Hamed Tabesh (Guilan University of Medical Sciences, 2016)
Abstract Introduction: Teenagers (especially girls) who are going through puberty are among vulnerable populations whose sexual needs receive little attention. Objective: This study aimed to determine educational needs of 11-14 year old girls on sexual health in Dezful. Methods: This cross-sectional study was conducted on 810 middle school girls aging 11 to 14 in Dezful city in 2012. Samples were selected by cluster sampling method. Data collection instrument was a researcher made questionnaire including 14 questions on demographic data and 46 questions on 4 domains of puberty, menstruation, sex relationship and reproduction using articles and resource reviews.Descriptive statistics and Chi-square, Kruskal-Wallis test were used for quantitative and qualitative data analysis. Results: The knowledge of girls on puberty, menstruation and reproductive was weak. Need to get information on puberty health (underwear wash with soap, shaving) and menstruation (age of menarche, menstruation blood source, dysmenorrhea) was 95/7% and 97/5% respectively. The most important source of information on puberty (51/1), menstruation (54/2%) mother, sexual activity (42/5%) friends and reproduction (32/1%) was sister. There was a significant correlation between mother's education level and need to obtain information on puberty, menstruation and reproduction using Chi-square test (P<0/05). Conclusion: In attention to the need for samples to receive information on sexual health and the role of mothers as the most important source of information to girls, people based training approaches (family education through health volunteers) is the best solution